Ιατρικές γνώσεις του Ρήγα Βελεστινλή στο έργο του "Φυσικής Απάνθισμα" - Καραμπερόπουλος, Δημήτριος Α. (2023)
Μετά από όσα αναφέρθηκαν μπορεί να λεχθεί συμπερασματικά ότι ο Ρήγας ήταν αρκετά ενημερωμένος πάνω στα ιατρικά θέματα. Είναι κι αυτό δείγμα τής δυναμικότητος του πνεύματός του, εντασσόμενο μέσα στο ευρύτερο περιβάλλον του διαφωτισμού, όπου ο Ρήγας κινείται και δρα. Summary: Rhigas Velestinlis had a good knowledge of anatomy and physiology, as seen in his issue «Φυσικής Απάνθισμα». More specifically Rhigas refers to: the conception and growth of the fetus; the delivery and its ubnormal condition; the eight months newborns and their ability to survive; the circulation of the blood and The function of the heart (as far as I know it is the first time that this subject is treated in a Greek edition); the cutaneous respiration; the theory of spotaneous generation; the bladder stone etc.